1995
DOI: 10.1136/thx.50.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian diet as a risk factor for tuberculosis in immigrant south London Asians.

Abstract: Background -In a previous retrospective study of tuberculosis in south London among Asian immigrants from the Indian subcontinent Hindu Asians were found to have a significantly increased risk for tuberculosis compared with Muslims. This finding has been further investigated by examining the role of socioeconomic and lifestyle variables, including diet, as risk factors for tuberculosis in Asian immigrants from the Indian subcontinent resident in south London. Methods -Using a case-control study technique Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 23 publications
(2 reference statements)
0
38
0
Order By: Relevance
“…Vegetarian diet may predispose to vitamin-D deficiency, and among immigrant south London Asians vegetarianism has been found to be a risk factor for tuberculosis. 110 Serum 25(OH)D 3 levels have been found to be lower among untreated tuberculosis patients than controls in the UK and to be associated with disease severity in tuberculosis patients in Indonesia. 111,112 Vitamin D exerts its effects via the vitamin-D receptor (VDR) which is present on monocytes and activated T and B lymphocytes.…”
Section: Vitamin-d Receptormentioning
confidence: 99%
“…Vegetarian diet may predispose to vitamin-D deficiency, and among immigrant south London Asians vegetarianism has been found to be a risk factor for tuberculosis. 110 Serum 25(OH)D 3 levels have been found to be lower among untreated tuberculosis patients than controls in the UK and to be associated with disease severity in tuberculosis patients in Indonesia. 111,112 Vitamin D exerts its effects via the vitamin-D receptor (VDR) which is present on monocytes and activated T and B lymphocytes.…”
Section: Vitamin-d Receptormentioning
confidence: 99%
“…We have shown that the susceptibility to both osteomalacia and tuberculosis in immigrant Asians from the Indian subcontinent is significantly greater in Hindu than Muslim subjects living in south London 3 4. For both osteomalacia and tuberculosis the increased risk seems to be explained by the higher prevalence of vegetarianism among Hindus.…”
mentioning
confidence: 79%
“…With the help of an Asian dietitian we identified all Asian names and categorised them as probable Hindu, probable Muslim, or other. This method has been shown to be accurate 4. Patients who were admitted more than once during the two years were counted only once.…”
mentioning
confidence: 99%
“…It is also associated with a vegetarian diet (32) in south Asian Hindus, thought to be the result of a deficiency of vitamin D to fight infection. (33) Asthma and respiratory diseases were significantly associated with a number of different environmental factors. Hospital admissions for asthma are shown in Figures 1 and 2.…”
Section: Health Outcomes and The Environmentmentioning
confidence: 99%